Management of isolated minor head injury in the UK. Issue 11 (3rd June 2010) - Goodacre, Steve W; Pandor, Abdullah; Pickering, Alastair
Abstract : Background: Recent guidelines and service developments may have changed the management of isolated minor head injuries in the UK. The authors aimed to review current practice and national statistics, and determine whether methods of service delivery are associated with differences in admission rates. Methods: The authors surveyed management of minor head injuries in all acute hospitals in the UK and then correlated these responses with Hospital Episodes Statistics (HES) emergency department data relating to head injury. Results: Responses relating to children were received from 174/250 hospitals and adults from 181/250. Nearly all hospitals had unrestricted access to CT scanning (adults 96%, children 94.5%). Most hospitals (70.1%) admitted adults under the emergency department staff, usually (61.4%) to an observation ward or clinical decision unit. Children were usually formally admitted to a ward (86.7%) under an inpatient team (78.5%). The median proportion of attendances admitted was higher for adults (18%) than for children (9%). There was no evidence of any association between the proportion admitted and the admission team, location or requirement for senior or specialist approval (all p>0.1). Conclusion: Minor head injury admission, especially for adults, is increasingly the responsibility of the emergency department. Admission policies had no significant effect on the proportion admitted, although improved HES data are required to confirm this.